Pichia acaciae Killer System: Genetic Analysis of Toxin Immunity - Paluszynski, John P; Klassen, Roland; Meinhardt, Friedhelm (Applied and Environmental Microbiology, 2007)
The gene responsible for self-protection in the Pichia acaciae killer plasmid system was identified by heterologous expression in Saccharomyces cerevisiae. Resistance profiling and conditional toxin/immunity coexpression analysis revealed dose-independent protection by pPac1-2 ORF4 and intracellular interference with toxin function, suggesting toxin reinternalization in immune killer cells.